High uric acid level increases the risk of acute kidney injury in acute coronary syndrome patients - Erny Puti; Haerani Rasyid; Pendrik Tandean; Himawan Sanusi; Hasyim Kasim; Syakib Bakri; Makbul Aman; Arifin Seweng (Babol University of Medical Sciences, 2021)
Background: Both clinical and experimental evidence have been published over the past few decades supporting the existence of a close relationship between the elevated levels of serum uric acid with cardiovascular events and acute kidney injury (AKI). This study aimed to determine the effect of serum uric acid levels on the incidence of AKI in acute coronary syndrome (ACS) patients. Methods: A retrospective cohort study with a cross sectional design was performed. The research was conducted at Dr. Wahidin Sudirohusodo Hospital from October 2019 to December 2019. Nonrandom sampling was employed in the medical records. All patients who met the inclusion criteria were at > 18 years old and diagnosed with ACS with AKI. The demographic data of age, sex and serum uric acid levels were recorded. The data obtained were analyzed using the SPSS (Statistical Package for Social Sciences). Results: There were 158 subjects of ACS patients with AKI and 135 without AKI. There was a significant correlation between high uric acid levels with the incidence of AKI in ACS (p<0.001). Patients with high serum uric acid levels were 9.5 times at risk of developing AKI compared to those with normal serum uric acid levels. Conclusion: High uric acid level is one of the risk factors for AKI in ACS and indicates 9.5 times at risk of developing AKI compared to normal serum uric acid level. Therefore, it is necessary to monitor serum uric acid level and kidney function in ACS patients.